2024
DOI: 10.3390/genes15030374
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Anticodon: tRNA Core Modifications and Their Impact on Structure, Translation and Stress Adaptation

Marcel-Joseph Yared,
Agathe Marcelot,
Pierre Barraud

Abstract: Transfer RNAs (tRNAs) are heavily decorated with post-transcriptional chemical modifications. Approximately 100 different modifications have been identified in tRNAs, and each tRNA typically contains 5–15 modifications that are incorporated at specific sites along the tRNA sequence. These modifications may be classified into two groups according to their position in the three-dimensional tRNA structure, i.e., modifications in the tRNA core and modifications in the anticodon-loop (ACL) region. Since many modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 177 publications
0
0
0
Order By: Relevance
“…Other factors that could offer tRNA Ala protection from MCP3 are tRNA modifications and the presence of other modified tRNA species. An open question in the field of trans -editing factors is whether tRNA modifications act as anti-determinants for proofreading ( Giegé and Eriani, 2023 ; Yared et al, 2024 ). Future work will determine the impact of the Tb MCP3 interactome and the role of post-transcriptional/translational modifications on the activity of this editing domain.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that could offer tRNA Ala protection from MCP3 are tRNA modifications and the presence of other modified tRNA species. An open question in the field of trans -editing factors is whether tRNA modifications act as anti-determinants for proofreading ( Giegé and Eriani, 2023 ; Yared et al, 2024 ). Future work will determine the impact of the Tb MCP3 interactome and the role of post-transcriptional/translational modifications on the activity of this editing domain.…”
Section: Discussionmentioning
confidence: 99%
“…tRNAs are frequently post-transcriptionally imbued with diverse modifications that drastically impact their structure and function ( Lorenz et al, 2017 ; Suzuki, 2021 ; Cappannini et al, 2024 ; Yared et al, 2024 ). tRNAs exhibit diverse modifications in all arms, but they are most frequent at the tRNA core and anticodon arm ( Cantara et al, 2011 ; Smith et al, 2024 ).…”
Section: Improving Codon-anticodon Interactionsmentioning
confidence: 99%
“…In fact, tRNAs are the most extensively modified cellular RNA with about 12% of nucleotides modified (an average of eight modifications per bacterial tRNA and 13 per eukaryotic ( Zhang et al, 2022 ) and around 100 distinct modifications identified in total ( Machnicka et al, 2014 ; Cappannini et al, 2024 ). Some bases like the 3′ CCA end and discriminator base are never modified, while others are modification hotspots, such as nucleotides in the elbow region ( Yared et al, 2024 ) and anticodon loop ( Lorenz et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%